(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Use of new pedagogical and technological methods in teaching history. The article says that the role of visual aids is very significant. It must be recognized as mandatory that any documentary illustration should be accompanied by some annotation, without which the teacher, who is not sufficiently familiar with the history of culture and art, will not be able to make out illustrations with the students.